The Influence of Accounting Students' Perceptions of the Auditor's Work Environment and Socio-Cultural Factors on Their Career Choices as Auditors - Saputra, Ebit Bimas; Desmiwerita, Desmiwerita (Dinasti Accounting Review, 2023)
This study aims to determine (1) the effect of accounting students' perceptions of the auditor's work environment on their career choices as auditors, (2) the influence of socio-cultural factors on their career choices as auditors, (3 Effects of accounting students' perceptions of the auditor's work environment and socio-cultural factors on the auditor's work environment). career choice as an auditor. This type of research is descriptive quantitative using a questionnaire method. The results show that (1) the work environment has a significant effect on career choice as an auditor. (2) socio-cultural factors have a significant effect on career choice as an auditor. (3) work environment and social value factors simultaneously influence career choice as an auditor.